Theoretical Foundations of the Concept of the Company's Competitiveness - Nizomiddinov Jahonmirzo Zukhriddinoglu (Research Parks Publishing LLC, 2022)
In the modern world, in the conditions of a transforming economy, the competitive environment is becoming more complex and dynamic. Many leading enterprises and companies have lost their advantage, unable to cope with the growing flow of competitors or with changing environmental conditions. The activities of enterprises are now influenced by many factors, so it is important to correctly determine the competitive advantages of the company, and on their basis to increase its competitiveness. Competitiveness in the market in today's economy is an important and basic quality of the company's commercial success. In turn, it depends on the quality of management and the competitiveness of finished products and services, that is, on the extent to which it is better than analogues - products and services offered by a competitor.